EFEKTIVITAS NPK GROWER DAN POC BONGGOL PISANG PADA PERTUMBUHAN BIBIT TANAMAN PISANG KEPOK (Musa paradisiaca) DENGAN TEKNIK BELAHAN BONGGOL - T. Rosmawaty; Raisa Baharuddin; Hendro Priono (DINAMIKA PERTANIAN, 2021)
The development of kepok bananas in Indonesia generally uses banana sapling, but this technique has weaknesses such as low uniformity and takes a long time. So, it is necessary to get the latest techniques such as the technique of splitting humps which is easier and cheaper. In addition, its development requires the balanced fertilization techniques using inorganic and organic fertilizers. This study aims to determine the effect of interaction and the main effect of NPK Grower and banana humps liquid organic fertilizer (LOF) on the growth of kepok banana seedlings (Musa paradisiaca) by using the splitting humps. This research was carried out at the Experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru City. The study was conducted from March to May 2021. The research design used a completely randomized design (CRD) with two factors. The first factor was the concentration of NPK Grower (G), which consisted of 4 levels, which were 0 g/plant, 15 g/plant, 30 g/plant, and 45 g/plant. The second factor was LOF banana humps (P), consisting of 4 levels, namely 0%, 15%, 30%, and 45% which consisted of 3 replications. The parameters observed were the percentage of growth, budding time, plant height, number of leaves, stem girth, longest leaf length, and widest leaf width. The data were statistically analyzed and continued with the honest significant difference test (HSD) at the 5% level. The results showed that there was a significant interaction between NPK Grower and banana humps LOF on the parameters of plant height, number of leaves, stem girth, longest leaf length, and widest leaf width. The best treatment was found in NPK Grower with a dose of 45 g/plant combined with a concentration of LOF banana humps of 300 ml/lair.